RELEVANSI AJARAN SOCRATES DALAM AGAMA HINDU - I Wayan Gata (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Humans as special beings created by God Almighty, have the potential that is not possessed by other creatures. With the potential of spirit, soul, and reason, humans are capable of becoming more noble beings than other creatures. Every activity of human life, the application of thinking is very necessary and will ultimately determine the results achieved. philosophy is a discipline that requires reflection and systematic systematic thinking by actively using intellect and reason, so philosophy is a good tool for understanding how to think. Socrates was one of the most famous philosophers throughout the history of philosophy. In this article, we will explain how the teachings of Socrates are related to the teachings of Hinduism which basically includes (1) tattwa; (2) ethics; (3) ritual / ceremony. Besides that, the core of the Socratic teachings is about ethics, namely glory or virtue, wisdom (wiweka) and leadership, to achieve the highest goal of human life, namely to make his soul as good as possible or happiness (eudaimonia) through the path of knowledge. The leadership he teaches cannot be separated from ethics. Socrates disagreed with the election of the leader with the most votes despite succeeding in building the economy but in his opinion the leader must be able to make his country in good condition. So that it can be said what was thought of Socrates in line with the teachings of Hinduism.